2020
DOI: 10.5603/pjnns.a2020.0017
|View full text |Cite
|
Sign up to set email alerts
|

Extent of anterior clinoidectomy for clipping of carotid-ophthalmic aneurysms predicted on three-dimensional computerised tomography angiography

Abstract: Aim of study. We aimed to verify the value of computerised tomography angiography (CTA) on predicting the extent of anterior clinoidectomy that is optimal for particular carotid-ophthalmic aneurysms (COAs).Clinical rationale for study. The anterior clinoid process (ACP) often impedes the complex microsurgery of COA. Complete removal of the ACP ensures safe clipping; however, it also may increase the risk of severe complications. The probability of performing a successful partial anterior clinoidectomy could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…This anatomical relationship significantly aided in deciding whether to remove the ACP in the surgical field. In some cases, 3D CTA with bone image enabled us to predict that aneurysm clipping could be performed without ACP removal and falciform ligament cutting [ 17 ]. If imaging showed that the aneurysm was located distal to the ACP, the aneurysm could likely be clipped without ACP removal.…”
Section: Discussionmentioning
confidence: 99%
“…This anatomical relationship significantly aided in deciding whether to remove the ACP in the surgical field. In some cases, 3D CTA with bone image enabled us to predict that aneurysm clipping could be performed without ACP removal and falciform ligament cutting [ 17 ]. If imaging showed that the aneurysm was located distal to the ACP, the aneurysm could likely be clipped without ACP removal.…”
Section: Discussionmentioning
confidence: 99%
“…Using the combination of minipterional approach (keyhole approach) with extradural resection of the anterior clinoid process (ACP) -an element of skull base surgery -we can significantly expand the range of indications for this approach. The main indications are: paraclinoid aneurysms of the internal carotid artery in patients having contraindications for endovascular treatment; small lesions of the sella turcica, the area of the sphenoid bone wings, and the anterior clinoid process; optic nerve gliomas; pathologies requiring decompression of the optic canal [7][8][9][10].…”
Section: List Of Abbreviation Acp -Anterior Clinoid Process Ica -Internal Carotid Arterymentioning
confidence: 99%
“…Depending on the location and degree of stenosis, the symptoms of CAC may manifest as hypertension, lower extremity arterial ischemia, heart failure, intracranial aneurysm rupture, etc. [2,3]. e cause of aortic constriction is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%